Analysis of the blood bacterial composition of patients with acute coronary syndrome and chronic coronary syndrome - Khan, Ikram; Khan, Imran; Usman, Muhammad; Jianye, Zhou; Wei, Zhang Xiao; Ping, Xie; Zhiqiang, Li; Lizhe, An (Frontiers in Cellular and Infection Microbiology, 2022)
Emerging evidence revealed that the blood microbiota plays a role in several non-communicable diseases, including cardiovascular disease. However, the role of circulating microbes in atherosclerosis remains understudied. To test this hypothesis, we performed this study to investigate the microbial profile in the blood of Chines atherosclerosis volunteers. A total of seventy Acute Coronary Syndrome (ACS) patients, seventy Chronic Coronary Syndrome (CCS) patients, and seventy healthy individuals were examined using high-throughput Illumina Novaseq targeting the V3-V4 regions of the 16S rRNA gene. The relationship between atherosclerosis and blood microbiome, clinical variables, and their functional pathways were also investigated. Our study observed significantly higher alpha diversity indices (Chao1, p = 0.001, and Shannon, p = 0.004) in the ACS group compared with CCS and healthy group, although a significantly lower alpha diversity was observed in the CCS compared to ACS and healthy group (p < 0.05). Beta diversity based on principal coordinate analysis demonstrated a major separation among the three groups. In addition, using linear discriminant analysis, a significant distinct taxon such as Actinobacteria _ phylum, and Staphylococcus¬¬¬_ genus in the healthy group; Firmicutes_ phylum, and Lactobacillus¬_ genus in the CCS group, and Proteobacteria and Acidobacteriota _ phyla in ACS group were observed among three groups. Furthermore, COG and KEGG pathways suggested a significant variation among all groups (p < 0.05). Additionally, some microbiota in the blood is closely associated with the clinical characteristics of atherosclerosis. Elucidating these differences in blood microbiomes will provide a foundation to improve our understanding of the role of microbiota in the pathogenesis of atherosclerosis.